Land Grading dengan Metode Plane of Best Fit untuk Pencetakan Sawah Baru - Damar Susilowati; Subari Subari; Muhammad Muqorrobin (Jurnal Irigasi, 2012)
To optimize the volume of cut and fills need to carry out Land Grading for new completed irrigation, therefore this report will discuss land grading for surface irrigation and its benefits and reasons for carrying this out. This report examines Land Grading using Plane of Best Fit method that have been used, with its advantages and disadvantages. Most of the advanced country conducted Land Consolidation for the new completed irrigation project. From the research result (Damar S., 1987) shows that Plane of Average Profile Method suitable for the area that have been consolidated, while Least Square Method can be used for any shape area. This report also covers some important factors that can seriously affect the costs of land grading such as suitability of site. This report discusses land grading by Plane of Best Fit Method using computer programs that is developed from Plane Method, because it is the fastest and most accurate results that can be achieved.